Analisa Perangkat Fortinet Sebagai Firewall Untuk Memblokir Aplikasi Sosial Media Dan Platform Streaming Saat Jam Kerja (Studi Kasus : PT. Aplikanusa Lintasarta) - Bayu Adi Prasetia; Delpian Attar Ramadhany; Guruh Guniawan; Iwan Giri Waluyo (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
This analysis focuses on testing computer network performance in terms of network security systems. The trial itself was carried out on a computer network in one of the network companies at PT. Aplikanusa Lintasarta uses the Fortinet operating system. The final result expected through this analysis is to look comprehensively at Fortinet's web filtering capabilities in overcoming the problem of blocking social media applications and streaming platforms during working hours. Blocking the application in question is the ability to filter web processes such as Facebook, Instagram, YouTube, etc. In the trials carried out, web filtering was able to block existing applications on social media and streaming platforms which proved that the performance of web filtering was quite good. In analyzing the performance of web filtering using the office hour rule tool by carrying out a rule schedule that is in the Fortinet network and displaying all information in detail. The final result obtained in the network filtering application simulation process using fortinet is that every network sent cannot enter (block) both social media applications and streaming platforms.